A CEP Peptide Receptor-Like Kinase Regulates Auxin Biosynthesis and Ethylene Signaling to Coordinate Root Growth and Symbiotic Nodulation in Medicago truncatula. Issue 9 (25th June 2020) - Zhu, Fugui; Deng, Jie; Chen, Hong; Liu, Peng; Zheng, Lihua; Ye, Qinyi; Li, Rui; Brault, Mathias; Wen, Jiangqi; Frugier, Florian; Dong, Jiangli; Wang, Tao
Abstract : Under nitrogen starvation, the COMPACT ROOT ARCHITECTURE2 pathway in Medicago truncatula coordinates root and nodule development through reducing auxin biosynthesis and inhibiting ethylene signaling. Abstract: Because of the large amount of energy consumed during symbiotic nitrogen fixation, legumes must balance growth and symbiotic nodulation. Both lateral roots and nodules form on the root system, and the developmental coordination of these organs under conditions of reduced nitrogen (N) availability remains elusive. We show that the Medicago truncatula COMPACT ROOT ARCHITECTURE2 (MtCRA2) receptor-like kinase is essential to promote the initiation of early symbiotic nodulation and to inhibit root growth in response to low N. C-TERMINALLY ENCODED PEPTIDE (MtCEP1) peptides can activate MtCRA2 under N-starvation conditions, leading to a repression of YUCCA2 ( MtYUC2 ) auxin biosynthesis gene expression, and therefore of auxin root responses. Accordingly, the compact root architecture phenotype of cra2 can be mimicked by an auxin treatment or by overexpressing MtYUC2, and conversely, a treatment with YUC inhibitors or an MtYUC2 knockout rescues the cra2 root phenotype. The MtCEP1-activated CRA2 can additionally interact with and phosphorylate the MtEIN2 ethylene signaling component at Ser 643 and Ser 924, preventing its cleavage and thereby repressing ethylene responses, thus locally promoting the root susceptibility to rhizobia. In agreement with this interaction, the cra2 low nodulation phenotype is rescued by an ein2 mutation. Overall, by reducing auxin biosynthesis and inhibiting ethylene signaling, the MtCEP1/MtCRA2 pathway balances root and nodule development under low-N conditions.